Unintended Lessons of Revolution : Student Teachers and Political Radicalism in Twentieth-Century Mexico. - Padilla, Tanalís. (Duke University Press, 2022)
Tanalís Padilla traces the history of the normales rurales--rural schools in Mexico that trained campesino teachers--and outlines how despite being intended to foster a modern, patriotic citizenry, they became sites of radical politics.